Urgensi Perkembangan Motorik Kasar Pada Perkembangan Anak Usia Dini - Aida Farida (Universitas Islam Negeri Sumatera Utara, 2016)
Growth and development is a whole matching in dyeing rate of child development day after day, month after month and year after year. We realize that both are important to a child's development in particular the physical development of the child. pemehaman will be harsh on the motor development of children will give you an idea on us about motor development of children's motor characteristic rough, rough children as well as the urgency of the development motor rough kids. At least the motor on rough urgency through appropriate actions in memaksimalkannya will have an impact on the incidence of self-confidence and emotional stability in children.